Parametric evaluation of S-CO2 Brayton cycles for bottoming applications - Brighenti, Giovanni; Anselmi Palma, Eduardo; Zachos, Pavlos K. (Cranfield University, 2016)
Parametric design studies for the preliminary assessment of physical footprint of Supercritical CO2 power plants are presented herein. The aim of the study is to quantify trade-offs between cycle efficiency and plant complexity for a range of S-CO2 cycle configurations.